The Effect of Internal Control, Professionalism, Pressure, and Anti-Fraud Awareness on Fraud Prevention - Veronika Rasdiana Toja; Ikhsan Budi Riharjo; Nur Handayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to examine the influence of internal control, professionalism, pressure and anti-fraud awareness as independent variables on fraud prevention as dependent variables. The object of this study is KSP Kopdit Pintu Air with the head office address at Rotat, Ladogahar Village, Nita District, Sikka Regency, East Nusa Tenggara. This type of research is causal comparative research (Causal-Comparative Research). This study's target population was KSP Kopdit Pintu Air employees with job levels as Internal Auditor and Manager with a sampling technique using the saturated sampling method. The number of samples in this study was 89 people. The type of data in this study is subject data (Self-Report Data) using primary data sources. The data collection technique for this study was carried out by distributing questionnaires to 89 respondents. The data analysis technique used multiple linear regression analysis. The results of the study showed that (1) internal control did not affect fraud prevention at KSP Kopdit Pintu Air; (2) professionalism had a positive effect on fraud prevention at KSP Kopdit Pintu Air; (3) pressure did not affect fraud prevention at KSP Kopdit Pintu Air; (4) Anti-fraud awareness has a positive influence on preventing fraud at KSP Kopdit Pintu Air.